Experiências de adequação sociotécnica e tecnologia social: análise da cooperativa de trabalho dos agentes ambientais de Pato Branco (PR) - Cavalheiro, Andrea Rafaela Royer (2019)
This study is about the Social Technology (ST) and Socio-technical Adequaty themes (STA). It is connected to the current discussions about regional development. The objective was to analyze the processes of technical appropriation, from the possible Sociotechnical Suitability and Social Technology experiences, in a recyclable materials collectors' cooperative. The theoretical subsidy base was: the modernity criticism, the conventional development, the relations between the STCs and the public policies. In this framework, the frantic race forward the economic growth, the unbridled nature usage and the social inequality increase put in question the man rationality and concepts such as: evolution, civilization, progress and development. Considering this context of inequalities and unsustainability, the present dissertation proposed to think about alternatives for the development from ST and STA. The research instruments used were: data analysis, focus groups and interviews, oriented by the experiences analyze method. This method has five dimensions: 1) Contextualization and Historical Description; 2) Technological Nature and Sociotechnical Environment; 3) Economic and Environmental Sustainability; 4) Institutional and Binding Arrangement; and 5) Policy or Prospecting Sustainability. The results sought to contribute to the ST and STAs theme as well to the development alternatives and the initiatives strengthening reflection such as the recyclable materials cooperative. Among the results it was possible to observe that the cooperative under study is composed of a certain workers collective with similar characteristics and associated with the exclusion factors adopted by the capitalist society (it predominates: female gender, brown or black race/color, low schooling, old age, low paid professional experience and high precariousness and peripheral regions inhabitants). The cooperative formation context showed to be involved in social issues, such as unemployment, low income and on political issues, for example how the municipality need to guarantee the Urban Solid Waste, collection and destination service, as well as to guarantee access to resources for this purpose, besides the environmental question that demanded demanded the integrated management of waste. This situation was observed as a timely and consolidated the cooperative formalization. As for the technological appropriation processes, it was characterized by the conventional model and the solidarity model hybridization. The cooperative alternates surpluses distribution experiences, assemblies, meetings, polling and mutual help, with knowledge hierarchy experiences and power asymmetries, with emphasis on the public power strong influence, since it is the largest and practically the unique partner: the city hall. In this sense, it was found limits on the ST experience, however, it was observed the STA Modes approximation (especially: Usage, Ownership and Work Process Adjustment). It has also been observed, through the analyzed experience, that technological transfers and non-contextualized replications are not sufficient for social transformation, but measures to encourage autonomy and emancipation are necessary, such as STA and political practices in the citizenship exercise struggle. This reinforces the STs need opinion as a public development policy. As limits suggest new studies, highlight the link with public policies and methodological improvement to analyze the perception of subjects to the need for ST/STA.